2015
DOI: 10.1007/s11187-015-9646-0
|View full text |Cite
|
Sign up to set email alerts
|

Subsidized start-ups out of unemployment: a comparison to regular business start-ups

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(50 citation statements)
references
References 46 publications
(43 reference statements)
1
36
0
2
Order By: Relevance
“…In these cases, individuals enter selfemployment to work longer hours but without increased monthly profits, suggesting a form of 'self-exploitation'. This reinforces earlier findings that have found that even when the unemployed become self-employed, their earnings are lower than those entering from employment or continuing in self-employment (Caliendo et al, 2015). These results provide a basis for identifying both positive and negative outcomes from self-employment.…”
Section: Discussionsupporting
confidence: 89%
“…In these cases, individuals enter selfemployment to work longer hours but without increased monthly profits, suggesting a form of 'self-exploitation'. This reinforces earlier findings that have found that even when the unemployed become self-employed, their earnings are lower than those entering from employment or continuing in self-employment (Caliendo et al, 2015). These results provide a basis for identifying both positive and negative outcomes from self-employment.…”
Section: Discussionsupporting
confidence: 89%
“…A study comparing subsidized start-ups by unemployed workers with regular start-ups after 19 months finds higher survival rates for the subsidized businesses but lower income, slower growth, and less innovation [5]. A study for France finds no significant effect on turnover or employment growth rates.…”
Section: Causal Effects On Employment Income and Business Growth Anmentioning
confidence: 97%
“…Providing start-up subsidies to unemployed workers is justified by the existence of constraints to unemployed workers starting a new enterprise [5]. Severe credit constraints are one problem.…”
Section: Start-up Subsidies Can Help Overcome Multiple Constraintsmentioning
confidence: 99%
See 2 more Smart Citations